Morus alba leaf extracts prevent indomethacin-induced intestinal ulcers via suppression of endoplasmic reticulum stress - Cherdsak Boonyong, Wannee Angkhasirisap, Nonthalert Lertnitikul, Kanchana Kengkoom, Rutt Suttisri, Suree Jianmongkol (Journal of Applied Pharmaceutical Science, 2025)
This study investigated the gastrointestinal (GI) protective effect of water and ethanol extracts of Morus alba leaves in rats who received indomethacin. Rats were randomly distributed into nine groups: a control group, an indomethacin group, and seven groups pre-treated orally with either water and ethanol extracts of M. alba leaves (500, 1,000, and 2,000 mg/kg) or omeprazole (100 mg/kg) for 5 days before receiving oral indomethacin (40 mg/kg). After 24-hour treatment, GI lesions, apoptotic proteins, and prostaglandin E2 (PGE2) in gastric and jejunal tissues were evaluated by macro- and microscopic assessments, western blot analysis, and ELISA, respectively. Both extracts prevented ulcerative lesions in rat jejunum, but not in the stomach. Their intestinal protection involved suppressing protein kinase R-like ER kinase/C/EBP homologous protein signaling and the Bcl-2-associated X protein/B-cell leukemia/lymphoma 2 protein (Bax/Bcl-2) ratio. Both extracts did not affect PGE2 levels in rat GI tissues, which might explain their inability to prevent gastric ulcers.
Keywords: Gastro-intestinal ulcers, mulberry leaves, NSAIDs, endoplasmic reticulum stress prevention, stress-induced apoptosis